Local Wisdom of ‘Wariga’ in the Palalindon Manuscript - Damayanti, Silvia; Ari Sulatri, Ni Luh Putu (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
Manuscript (Balinese: lontar) as one of the wealth and treasure owned by the Balinese people store various traditional knowledge regarding various aspects of people's lives. This study examined the local wisdom contained in the Palalindon manuscript. The purpose of this study was to determine the local wisdom contained in the Palalindon Manuscript. The research method was carried out qualitatively and the data were collected using the library method. The data were analyzed using the theory of Literary Anthropology. The results of the study discovered that the Palalindon manuscript contains local wisdom of traditional Balinese people related to the Wariga belief in good and bad days which stems from the teachings of Jyotisa. Wariga or the calculation of good and bad daily activities of traditional Balinese people in Palalindon manuscript can be used as guidelines for Balinese people these days and in the future. This study with full of hope can be useful for Balinese people in understanding the noble values of their predecessors